2019
DOI: 10.1002/berj.3545
|View full text |Cite
|
Sign up to set email alerts
|

Private tutoring in a high socio‐economic secondary school in Israel and pupils’ attitudes towards school learning: A double‐edged sword phenomenon

Abstract: Private tutoring (PT) is a widespread educational phenomenon that blurs the conceptual boundaries of public and private education and can affect the formal school system and teachers’ work. This study examined whether participation in PT and the estimation of private tutors’ contributions are related to pupils’ attitudes towards teachers’ effectiveness. Based on a questionnaire administered to all pupils (n = 855) from Grades 7 to 10 from one secondary school located in an affluent area at the centre of Israel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 67 publications
(108 reference statements)
1
1
0
Order By: Relevance
“…Often, such motives are a reflection of what caused students to turn to shadow education in the first place. Hajar (2018), for example, found that students attended shadow education with the relatively proximal motive of passing school exams, and these findings were consistent across interview studies in Bangladesh (Mahmud, 2019), China (Yung, 2015), Israel (Addi-Raccah, 2019), and Japan (Ozaki, 2015).…”
Section: Students' Goalssupporting
confidence: 54%
“…Often, such motives are a reflection of what caused students to turn to shadow education in the first place. Hajar (2018), for example, found that students attended shadow education with the relatively proximal motive of passing school exams, and these findings were consistent across interview studies in Bangladesh (Mahmud, 2019), China (Yung, 2015), Israel (Addi-Raccah, 2019), and Japan (Ozaki, 2015).…”
Section: Students' Goalssupporting
confidence: 54%
“…both tangible and intangible impact of PT). As Addi‐Raccah (, p. 6) remarks, PT should not be perceived as ‘just a supplement that leaves the school system unchanged, but rather PT may challenge schools to take into account new institutional arrangements'. Therefore, influential actors in formal education settings should adapt to changes occurring outside their boundaries, and attempt to address perceived deficits in practice, both pragmatically and strategically.…”
Section: Resultsmentioning
confidence: 99%